Efficacy and Safety of Ascites Treatment in Liver Cirrhosis - G. A. Ignatenko; T. E. Kugler; G. G. Taradin; I. V. Rakitskaya; A. A. Kaluga (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Cirrhosis is one of the major health problems worldwide; and ascites is often its first and foremost manifestation. Despite the advances in modern hepatology, the presence of ascites is associated with a poor prognosis and high mortality. The aim of the study was to analyse data on the efficacy and safety of ascites treatment options, taking into account the pathophysiology of the condition. The analysis of literature and international guidelines on ascites management showed that cirrhotic ascites is treated with medication or surgery that interfere with pathogenetic mechanisms underlying the condition. Treatment of uncomplicated ascites depends on the severity of clinical manifestations. Patients with grade 1 ascites do not require treatment. Therapy for grade 2-3 ascites is aimed at reducing sodium intake and promoting its excretion with diuretics. The effect of diuretics should be assessed by daily monitoring of body weight. Close monitoring of serum creatinine and electrolyte levels is necessary to avoid severe electrolyte imbalance and mitigate the risk of diuretic-associated acute kidney injury. Another medical option to increase diuresis is the use of vasoconstrictors. Large volume paracentesis is the treatment of choice for patients with grade 3 ascites and refractory ascites. The most dangerous complication of paracentesis is circulatory dysfunction, which is prevented by limiting the volume of fluid removed to 5-6 liters per procedure and using plasma substitutes. If paracentesis is ineffective, new minimally invasive methods of treatment should be considered: transjugular intrahepatic portosystemic shunting and automated low-flow ascitic fluid removal system. However, given the poor prognosis, all patients with refractory ascites should be considered candidates for liver transplantation, which is currently the only effective treatment. The efficacy and safety of therapy may be enhanced by a personalised approach to choosing the treatment for ascites in cirrhosis, as well as further investigation of means to mitigate adverse reactions to medication and minimally invasive surgery.